Profitabilitas, Likuiditas, Kebijakan Dividen dan Peran Ukuran Perusahaan dalam Perusahaan Perbankan - Bhuana, Kadek Wisnu (JURNAL ONLINE INSAN AKUNTAN; Vol 9 No 2 (2024): Jurnal Online Insan Akuntan (Desember 2024), 2024)
This research analyzes the influence of profitability, liquidity and dividend policy in the context of the Indonesian banking sector, by considering company size as a moderating variable. This study focuses on the 2020-2024 period to capture the dynamics of the banking sector during the COVID-19 pandemic and post-pandemic. The research uses a quantitative approach with explanatory methods to test the relationship between independent, dependent and moderating variables. The results show that profitability and liquidity influence dividend policy differently, depending on the moderating role of firm size. These findings are relevant to agency theory, signal theory, and trade-off theory, and provide important insights for dividend policy management in the banking sector. This study highlights the importance of company size in determining dividend policy, both directly and as a moderator of profitability and liquidity.   Keywords : Profitability, Liquidity, Dividend Policy, Company Size, Indonesian Banking